Covariant spectator theory for the electromagnetic three-nucleon form factors: Complete impulse approximation - Pinto, Sérgio Alexandre (2009)
We present the first calculations of the electromagnetic form factors of 3 He and 3 H within the framework of the Covariant Spectator Theory (CST). This first exploratory study concentrates on the sensitivity of the form factors to the strength of the scalar meson-nucleon off-shell coupling, known from previous studies to have a strong influence on the three-body binding energy. Results presented here were obtained using the complete impulse approximation (CIA), which includes contributions of relativistic origin that appear as two-body corrections in a nonrelativistic framework, such as “Z-graphs,” but omits other two and three-body currents. We compare our results to nonrelativistic calculations augmented by relativistic corrections of O(v/c)2.